The Impact of COVID‐19 on the Technology Sector: The Case of Turkish Consultancy Company - GÖZÜTOK, EDA (İstanbul Kültür Üniversitesi, 2022)
Since COVID-19 emerged in Wuhan, China, it has affected the whole world both economically and sociologically. Many studies have been published by making different analysis studies and surveys to understand their positive or negative effects. It seemed different effects in terms of country and sector. In this study, the effects of COVID-19 on a consulting company serving in the field of technology were investigated. Using the company's five-year sales data from the pre-COVID-19 period, sales data for the COVID-19 period were predicted by machine learning over KNIME. Predictions were made using three different regression models: linear, gradient boosting, and random forest. Each model was compared over the calculated coefficient of determination (R2) and the best model was selected. With this chosen model, the impact of COVID-19 on the company has been interpreted.
Covıd-19'un Teknoloji Sektörüne Etkisi: Türk Danışmanlık Şirketi Örneği
▪ Yüksek lisans tezi.